2020
DOI: 10.1371/journal.pone.0244128
|View full text |Cite
|
Sign up to set email alerts
|

The use of methylprednisolone in COVID-19 patients: A propensity score matched retrospective cohort study

Abstract: Purpose To evaluate the efficacy and safety of methylprednisolone in treating the coronavirus disease 2019 (COVID-19) patients. Methods A retrospective cohort study was conducted, and all COVID-19 patients were recruited who were admitted to the Yichang Third People’s Hospital from February 1st to March 31st, 2020. One-to-one propensity score matching (PSM) was used for minimizing confounding effects. The primary outcome was hospital mortality, with the secondary outcomes being the time needed for a positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 15 publications
0
21
0
1
Order By: Relevance
“…RT-PCR showed negative for SARS-CoV-2 on hospitalization day 10 in this patient, which was different from the previous study by You et al (2020) that stated methylprednisolone could not improve the prognosis of patients with COVID-19. Another study stated that patients without the use of methylprednisolone were more quickly to obtain negative results (11 days) of their nasopharyngeal swab tests of SARS-CoV-2 nucleic acid after treatment, compared to those receiving methylprednisolone (13.5 days) [24] .…”
Section: Discussionmentioning
confidence: 99%
“…RT-PCR showed negative for SARS-CoV-2 on hospitalization day 10 in this patient, which was different from the previous study by You et al (2020) that stated methylprednisolone could not improve the prognosis of patients with COVID-19. Another study stated that patients without the use of methylprednisolone were more quickly to obtain negative results (11 days) of their nasopharyngeal swab tests of SARS-CoV-2 nucleic acid after treatment, compared to those receiving methylprednisolone (13.5 days) [24] .…”
Section: Discussionmentioning
confidence: 99%
“…The results of three meta-analysis further support the employ of systemic corticosteroids in COVID-19 pneumonia, but it is worth to mention that the weight of RECOVERY PLOS ONE trial was more than 50 per cent in all of them and the magnitude of the effect was modest (OR ranging from 0.70 to 0.88) [41][42][43]. On the other hand, several propensity score matching (PSM) studies found no impact of corticosteroids on COVID-19 pneumonia outcome [44][45][46][47][48][49], while an increased mortality was observed in other report [50] and two additional PSM studies concluded that corticosteroid therapy was associated with lower mortality [51,52]. Therefore, considering all the available evidence, the role of corticosteroids remains controversial in non-critically ill patients who need supplemental oxygen.…”
Section: Risk Factors For Unfavorable Outcomementioning
confidence: 87%
“…Sensitivity analysis for betweenstudy heterogeneity and analytical methods was performed to show the robustness of the finding. e analysis showed that the result was stable except for the exclusion of three studies [18,21,33] that changed the conclusion (Figure 7). e rationale for the use of corticosteroids is to decrease the host inflammatory responses in the lungs, which may lead to acute lung injury and acute respiratory distress syndrome [6].…”
Section: Sensitivity Analysismentioning
confidence: 93%
“…In the 26 included studies [17-19, 21-23, 25-30, 32-35, 37-42, 44, 45, 47, 48] with 13,565 patients, there were no significant differences in mortality between the steroid and nonsteroid treatment groups (RR � 0.95; 95% CI: 0.80-1.13; p � 0.57, I 2 � 78%, p < 0.0001) (Figure 2). e sensitivity analysis showed that the exclusion of three studies [18,21,33] changed the above conclusion.…”
Section: Mortality Associated With Steroid Use In Patients Withmentioning
confidence: 96%